THE EFFECTIVENESS OF MUCOADHESIVE AND MOUTHWASH THERAPY FOR ORAL MUCOSITIS WITH SYNTHETIC AND HERBAL INGREDIENTS: A SYSTEMATIC REVIEW AND META-ANALYSIS - KARINA, DHINI; SUFIAWATI, IRNA; RAMAMOORTHY, VATCHALA RANI (International Journal of Applied Pharmaceutics, 2024)
This study aimed to evaluate the effectiveness of herbal and synthetic mucoadhesive formulations and mouthwashes to reduce the grade and pain of Oral Mucositis (OM) through a systematic review and meta-analysis. Selection of articles published between 2014 and 2023 using Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) with specific keywords and through electronic databases (PubMed, Cochrane, Scopus, and Google Scholar) was carried out. Inclusion and exclusion criteria were established to limit the search for articles. The quality assessment of the articles used the Oxford Quality Scoring System. All 22 articles could be assessed by systematic review, but only 16 articles could be meta-analysis. The meta-analysis assessment used Jeffreys's Amazing Statistics Program (JASP) software. The mucoadhesive formulations of 1% Satureja hortensis extract gel, phenytoin tablets, 3% Chamomile topical gel and the mouthwash consisting morphine 2%, povidone-iodine 10 ml, turmeric, dentoxol, zinc chloride, sodium bicarbonate had affected to reduce the degree and pain of OM. Meta-analysis showed mucoadhesive had a mean effect size of -0.06 on the grade and -0.12 on the pain of the OM, while mouthwash had a mean effect size of -1.27 on the grade and -1.64 on the pain of the OM. To conclude, mucoadhesive formulations and mouthwashes have the potential to reduce the grade and pain of OM.